Point-of-Care Ultrasound Diagnosis of Traumatic Abdominal Wall Hernia. Issue 5 (May 2017) - Bjork, Lori B.; Bellew, Shawna D.; Kummer, Tobias
Abstract : Abstract: Traumatic abdominal wall hernias due to blunt abdominal trauma in pediatric patients can pose a diagnostic challenge because of spontaneous hernia reduction. Ultrasonography may be superior to computed tomography for this indication in some cases because of the ability to dynamically and repeatedly assess the area of injury. Herniation can be induced or exaggerated via Valsalva maneuvers, which can facilitate its detection during dynamic assessment. We present the case of a 3-year-old boy who sustained blunt abdominal trauma, with a resultant abdominal wall hernia that was diagnosed using point-of-care ultrasound imaging. This hernia was not visualized with computed tomography, and point-of-care ultrasonography expedited admission for operative repair.